Comparative evaluation on rheology performance and thermal stability of ester based drilling fluids. (November 2019) - Mohamad Daud, A R; Abdullah, S; Azizi, A; Ariyanto, E
Abstract: Drilling fluid plays an important role in ensuring smooth drilling operations. Application of ester based drilling fluid (EBDF) is desirable as it shows comparable performance to the conventional oil based drilling fluid (OBDF) as well as environmental friendly. The ester used as a base in the EBDF is usually derived from vegetable oils such as palm oil. In this study, methyl laurate (ML), methyl palmitate (MP), and isopropyl laurate (IPL) esters were used as a base in the EBDF formulation. Subsequently, their physical and rheological properties were determined. In addition, thermal stability of the EBDF was tested to estimate the maximum operating temperature for the EBDF application. Isopropyl laurate (IPL) based EDBF was found to have better rheological properties at standard test condition as compared to the other two esters used. The IPL based EBDF also showed improved viscosity at 90°C. Thermal stability test conducted on the IPL drilling fluid indicated that it is stable up to 150°C.